Analysis of The Relationship Between Complementary Feeding Practice and Parenting Style with the Nutritional Status of Children Aged 6-24 Months - Fergita, Agnestya Nurul; Kamsiah; Vaulinne Basyir; Arni Amir (JURNAL KEBIDANAN, 2025)
The nutritional status of children is currently a global concern, with two million children under the age of five suffering from severe acute malnutrition, a lifethreatening condition if left untreated. Millions of Indonesian children remain at risk due to high rates of stunting and wasting, as well as the double burden of malnutrition, where both undernutrition and overnutrition occur. Globally in 2020 (WHO), 149.2 million children under the age of five (22%) were stunted, 45.4 million children (6.7%) were wasted, and 38.9 million children (5.7%) were overweight. The purpose of this study was to analyze the relationship between complementary feeding practices and parenting patterns with the nutritional status of children aged 6– 24 months in the Pegambiran Health Center working area in Padang City. Study method is a quantitative research method with a cross-sectional study design. The results of the statistical analysis in this study using the chi- square test showed a significant association between complementary feeding practices and the nutritional status of children aged 6– 24 months (p- value = 0.000) and between parenting styles and the nutritional status of children aged 6– 24 months (p- value = 0.000). The conclusion of this study is that there is a relationship between the practice of providing complementary foods and the nutritional status of children aged 6– 24 months.